2023
DOI: 10.1002/smll.202206821
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Gd Nanoprobes for Self‐Confirmative MRI with Robust Stability

Abstract: which could exacerbate nephrogenic systemic fibrosis, and deposit in the heart, kidney, skin and even in the brain, threatening the patient's health. [5] To overcome these shortcomings, Gdbased inorganic nanoparticles (NPs), such as Gd 2 O 3 , [6] NaGdF 4 , [7] Gd-doped oxide, [8] were reported on account of the higher stability of Gd 3+ ions in Gd NPs-based CAs. The unsaturated coordination properties of Gd 3+ exposed at the NPs surface can be used to increase the hydration sites, which contribute to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Gadolinium-based chelates, renowned for their capability to shorten T1 relaxation times, are widely utilized in MRI imaging [ 36 ]. The effectiveness of imaging is closely linked to the concentration of gadolinium ions [ 36 , 37 ]. In our investigation, although the MRI imaging performance of PGd@tNBs particles with a gadolinium ion concentration of 0.5 mM falls short of that observed with a pure DTPA-Gd solution, it still suffices to generate contrast against the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gadolinium-based chelates, renowned for their capability to shorten T1 relaxation times, are widely utilized in MRI imaging [ 36 ]. The effectiveness of imaging is closely linked to the concentration of gadolinium ions [ 36 , 37 ]. In our investigation, although the MRI imaging performance of PGd@tNBs particles with a gadolinium ion concentration of 0.5 mM falls short of that observed with a pure DTPA-Gd solution, it still suffices to generate contrast against the control group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, single-atom materials that involve isolated metal atoms stabilized on a suitable carbon matrix have been extensively studied in catalysis and biomedical fields, primarily as single-atom nanozymes (SAzymes). , Due to their definite composition and geometric structure, those SAzymes are synthesized to maximize the enzyme-like catalytic activity and chemodynamic therapy (CDT) effect . Ji et al reported an iron-based SAzyme that exhibited superior peroxidase-like activity owing to the optimized Fe–N 3 P coordinated structure and showed excellent CDT efficiency.…”
mentioning
confidence: 99%
“…1,2 It offers real-time images with high sensitivity and high spatio-temporal resolution, which provides a new possibility for the conventional imaging methods, such as magnetic resonance imaging (MRI), ultrasound imaging (UI), positron emission tomography (PET) and computed tomography (CT). 3–8 However, short-wavelength ultraviolet-visible light is easily scattered or absorbed by biological tissues, leading to a poor tissue penetration. Near-infrared (NIR) light can overcome this drawback and has been widely used in fluorescence imaging in vivo .…”
mentioning
confidence: 99%